Terracing and ridge planting enhances soil organic carbon stability on water-eroded farmland slopes in Northeast China - Zhu Zhengqing; Mark Henderson; Gu Ruiting; Zhang Zhi; Zheng Xiaotong; Gong Xiaojing; Li Shang; Zhang Jiaqi; Liu Binhui (CATENA, 2026)

Experimental investigation of ethane(R170) solubility in AB, PAG, and POE lubricants - Ruiting Lv; Ruikang Li; Zhihao Zhang; Jialiang Hua; Guogeng He (International Journal of Refrigeration, 2026)

Endoplasmic reticulum stress-mediated glycophagy drives macrophage M1 polarization in silica nanoparticles-induced pulmonary fibrosis - Lei Bao; Zihan Geng; Linpeng Niu; Lili Shi; Liyi He; Yaxian Pang; Cunhui Zhang; Yan Liu; Jiawei Chen; Beibei Shi; Ruiting Wu; Jingyuan Wang; et al. (Journal of Environmental Sciences, 2026)

Seed-associated Pseudomonas enhance the growth of Ambrosia trifida - Xue Chen; Chunying Li; Chang Wang; Jieyu Yang; Ruiting Ju; Fengjuan Zhang; Jihua Wu (Plant and Soil, 2026)

Haplotype-resolved long-read sequencing reveals parent-of-origin effects of tandem-repeat variation in autism spectrum disorder - Jinchen Li; Tengfei Luo; Xue Ren; Songyu Yang; Hui Quan; Yan Zhu; Senwei Tan; Xiangbin Jia; Pei Yu; Yuanfeng Huang; Zhaowei Jiang; Xudong Xiang; et al. (Science Bulletin, 2026)

Acetic Acid Suppresses Perennial Ryegrass Growth In Vitro by Disrupting Gibberellin and Auxin Homeostasis and Restricting Cell Expansion - Hao Guan; Caiyi Xie; Weiyu Jia; Ruiting Ouyang; Yuhan Xia; Yuhan Fu; Yi Man; Huaiyang Hou; Yingjun Chi; Bin Xu; Jing Zhang (Journal of Plant Growth Regulation, 2026)

Corrigendum to “Development of active sustainable films based on phytic acid and silicate/polyvinyl alcohol hybrid system for wrapping chicken meat” [Food Packaging and Shelf Life 54 (2026) 101720] - Chaoqun Li; Fanyu Meng; Yongyan Yang; Jingfei Wang; Ruiting Zhang; Chongruihan Li; Yue Wang; Jia Wang; Yan Gao; Shuangling Zhong; Xuejun Cui (Food Packaging and Shelf Life, 2026)

Dynamic polysaccharide-based organic nanocomposite hydrogel precisely mediates oral targeted therapy for colorectal cancer - Xinyang Chen; Nuo Li; Huazheng Cheng; Ying Zhang; Ruiting Pan; Qin Shen; Guoqing Yan (Carbohydrate Polymers, 2026)

The role of easily biodegradable organic materials as soil biostimulants in mediating the rapid enhancement of soil aggregate stability - Zheng MA; Xinlei ZHANG; Yujian WANG; Luyao YANG; Ruiting GUO; Longtao TU; Zhenlun LI (Pedosphere, 2026)

Development of active sustainable films based on phytic acid and silicate/polyvinyl alcohol hybrid system for wrapping chicken meat - Chaoqun Li; Fanyu Meng; Yongyan Yang; Jingfei Wang; Ruiting Zhang; Chongruihan Li; Yue Wang; Jia Wang; Yan Gao; Shuangling Zhong; Xuejun Cui (Food Packaging and Shelf Life, 2026)

Biodegradable cellulose-based electrostatically assisted air filter with high filtration efficiency and low resistance for sub-micron PMs - Jingyi Nie; Yueqing Li; Tingting Jiao; Ruiting Yang; Meiyun Zhang (Chemical Engineering Journal, 2026)

Phage-based biosensors: From recognition to signal transduction empowered by amplification strategies for detecting foodborne pathogens - Fan Li; Xinxin Jiang; Yizhao Zhang; Ruiting Yao; Haorui Zhu; Lihua Fan; Guoliang Li (Trends in Food Science & Technology, 2026)

Deciphering the impacts of multi-source materials on semi-continuous anaerobic digestion of food waste: performance enhancement and mechanism analysis - Yongdong Chen; Ruiting Zhu; Fang Liu; Xiuxia Zhang; Shi Li; Li Gu; Jiancheng Shu (Journal of Environmental Management, 2026)

Repurposing hydrothermal carbonization aqueous product: Leveraging nitrification inhibition to drive a stable assimilatory metabolism for nutrient recovery - Ruiting Zhang; Hong Chen; Jun Sheng; Shiyi Zhao; Xin Yu; Dong Cheng; Hanyue Wu; Xiaoming Zou; Gang Xue (Chemical Engineering Journal, 2026)

Retraction notice to “Construction of functional curdlan hydrogels with bio-inspired polydopamine for synergistic periodontal antibacterial therapeutics” [Carbohydrate Polymers 245 (2020) 116585] - Xianqin Tong; Xiaoliang Qi; Ruiting Mao; Wenhao Pan; Mengying Zhang; Xuan Wu; Gang Chen; Jianliang Shen; Hui Deng; Rongdang Hu (Carbohydrate Polymers, 2026)

Astrocytic HMGCR-Mediated Cholesterol Alleviated Parkinson’s Disease Phenotypes by Inhibiting NF-κB Neuroinflammation - Xiaofeng Tian; Qing Liu; Jiacheng Zhang; Huijiao Du; Zhaoran Wei; Linjie Sun; Jiamin Gao; Ruiting Zhao; Lei Wang; Yizhou Zhang (Molecular Neurobiology, 2026)

The interaction between Ir nanocrystallites and Ni2P nanosheets regulates the adsorption energetics of intermediates for boosting ethanol electrolysis - Xiaoyu Zhang; Ruiting Chen; Ge Ma; Xin Wang; Yu Chen; Zhongwei Chen (Chemical Engineering Journal, 2025)

Revealing the nano-empowered fluorescent sensor arrays for the food safety point-of-care testing: An overview of mechanism and applications - Yaodong Guo; Xiaowen Zhang; Ruiting Wang; Jianlong Wang (Trends in Food Science & Technology, 2025)

Insight into using a novel ultrasound followed by peracetic acid / ultraviolet disinfection system to inactivate microorganisms in sewage based on synergy and metagenomics - Zhi Zhang; Yun Bai; Ruiting Chang; Xueli Hu; Juanjuan Yao (Journal of Water Process Engineering, 2025)

Invasion legacy weakens the positive effect of plant genotype diversity on soil multifunctionality - Wei Song; Cai Cheng; Zekang Liu; Shumeng He; Shenggui Xue; Xue Chen; Jingru Zhang; Lejie Wu; Qun Zhang; Guiyao Zhou; Yann Hautier; Ruiting Ju; et al. (Plant and Soil, 2025)

Carbon black induced pulmonary fibrosis through piR-713551/PIWIL4 targeting THBS2 signal pathway - Mengruo Wang; Yong Niu; Qingping Liu; Peihao Yang; Mengqi Wu; Ruiting Wu; Beibei Shi; Jiawei Chen; Jingyuan Wang; Zhe Du; Yaxian Pang; Lei Bao; et al. (Journal of Environmental Sciences, 2025)

Integrating photo-Fenton-like Fe3O4/CdS-O modules into sponge-based gel solar evaporator for synergistic water regeneration and pollutant degradation - Xuyao Qiao; Shuguang Ning; Hongyao Zhao; Ruiting Ni; Wanyu Zhang; Yangping Zhang; Linzhi Zhai; Danhong Shang; Yanyun Wang; Tongyi Yang; Mengnan Wang; Fu Yang (Journal of Environmental Chemical Engineering, 2025)

Enabling kinetics matching in electrocatalytic ammonia synthesis by leveraging spatially-confined Cu/Fe2O3 heterointerfaces to maximize *H supply and utilization - Mengting Liu; Fu Yang; Hongyao Zhao; Xiu Zhong; Ruiting Ni; Kwame Nana Opoku; Zhenxiao Wang; Yangping Zhang; Yanyun Wang; Feng Zeng; Yinlong Zhu; Weidong Shi (Chemical Engineering Journal, 2025)

Biodegradable air filter with electrospun composite nanofibers and cellulose fibers dual network: Enhanced electrostatic adsorption, humidity resistance, and extended service life - Jingyi Nie; Binrong Sun; Tingting Jiao; Jianfei Liao; Meiyun Zhang; Ruiting Yang; Yueqing Li (Journal of Hazardous Materials, 2025)

Foxp3 inhibits PCV2 replication by reducing the ATPase activity of Rep - Ruijiao Jiang; Qiuyan Huang; Ruiting Shen; Yongning Zhang; Lei Zhou; Xinna Ge; Jun Han; Xin Guo; Hanchun Yang (Veterinary Microbiology, 2025)

Vacancy engineering in transition metal selenides for long-lasting and fast-charging Na-ion batteries - Changsheng An; Jialing Liu; Chen Xu; Chi Zhang; Ruiting Li; Shumin Zhang; Shiying Zhang; Jinbo Li; Chao Cai; Xing Ou (Chemical Engineering Journal, 2025)

Reliability assessment of using different heavy metals in remote sedimentary records to reconstruct historical pollution - Jiapeng Gao; Ruiting Song; Xinrui Wang; Kexin Wan; Jianle Zhang; Guanqi Shan; Dejun Wan; Shaogang Wang (Environmental Pollution, 2025)

Electron-deficient asymmetric Co centers marry oxygen vacancy for NO3RR: Excellent activity and anion resistance property - Hao Lu; Kwame Nana Opoku; Zhenxiao Wang; Ruiting Ni; Mengting Liu; Yanyun Wang; Yangping Zhang; Chao Yu; Aihua Yuan; Fu Yang; Weidong Shi (Chemical Engineering Journal, 2025)

Ubiquitin-conjugating enzyme E2T confers chemoresistance of colorectal cancer by enhancing the signal propagation of Wnt/β-catenin pathway in an ERK-dependent manner - Bo Liu; Ruiting Liu; Xiaolong Zhang; Lifei Tian; Zeyu Li; Jiao Yu (Chemico-Biological Interactions, 2025)

Halobacillus rhizosphaerae sp. nov., a moderately halophilic bacterium with protease activities isolated from the rhizosphere soil of the mangrove Acanthus ebracteatus - Doudou Yin; Junjie Xie; Rui Liu; Chaodong Song; Ying Liang; Hongzhi Huang; Yihui Huang; Ruiting Long; Naikun Shen; Bing Yan; Hongyan Zhang (Antonie van Leeuwenhoek, 2025)

Cropland Exposure to Extreme Dryness and Wetness in China Under Shared Socioeconomic Pathways - Ruiting Yang; Guojie Wang; Yunxia Zhang; Peng Zhang; Shijie Li; Pedro Cabral (International Journal of Climatology, 2025)
Global warming by human activities have exacerbated the occurrence of extreme climatic events, which have taken a huge toll on human production and livelihoods. Predicting future changes in extreme wetness and dryness, along with the extent of cropland exposure to these conditions under various scenarios, is essential for effective climate adaptation and achieving sustainable development goals. This study employs the Standardised Antecedent Precipitation Evapotranspiration Index (SAPEI) method to identify extreme dryness and extreme wetness in China for future projections (2021–2100), and to analyse the characteristics of changes in the pixel‐day, intensity, and affected area by extreme dryness and wetness, as well as the cropland exposures to them under different shared socioeconomic pathways (SSPs). We find that the intensity and spatial extent of extreme dryness and wetness significantly increase in future climate projections, especially under high‐emission scenario compared to low‐emission scenario. Under the scenarios with increased emissions, the cropland exposure increased in most parts of China. Therefore, it is particularly urgent to keep the low‐emission scenario in order to minimise the cropland damage caused by extreme drought and wetness in China in the future.

Sulfur cycle, a new opportunity for nitrogen removal from textile wastewater: A review - Shiyi Zhao; Hong Chen; Jun Sheng; Xin Yu; Kejia Zeng; Dong Cheng; Hanyue Wu; Ruiting Zhang; Xianbao Xu; Xiaoming Zou; Gang Xue (Journal of Water Process Engineering, 2024)

Response mechanisms of submerged macrophytes and epiphytic biofilms to single and coexisting per-and poly-fluoroalkyl substances and antibiotics stress - Yakun Feng; Cuiling Jiang; Wei Zhang; Lei Sun; Zequn Fan; Can Lu; Lei Jiang; Ruiting Xu; Ya Liu (Journal of Environmental Chemical Engineering, 2024)

A multi-layer antimicrobial cellulose filter with electrostatic adsorption properties prepared by coating cellulose with chitosan and CuO - Jingyi Nie; Jianfei Liao; Tintin Jiao; Binron Sun; Meiyun Zhang; Ruiting Yang; Yueqing Li (Chemical Engineering Journal, 2024)

Layered deposited MoS2 nanosheets on acorn leaf like CdS as an efficient anti-photocorrosion photocatalyst for hydrogen production - Yao Wang; Tengyang Gao; Ruiting Li; Yan Chen; Wen Luo; Yang Wu; Yu Xie; Yong Wang; Yifan Zhang (Fuel, 2024)

Associations of environmental cadmium exposure with kidney damage: Exploring mediating DNA methylation sites in Chinese adults - Yuan Wei; Xiaochen Wang; Qi Sun; Wanying Shi; Wenli Zhang; Xu Gao; Yawei Li; Ruiting Hao; Xiaojie Dong; Chen Chen; Kangning Cao; Weilong Jiang; et al. (Environmental Research, 2024)

Transcriptome and small RNA analysis unveils novel insights into the C4 gene regulation in sugarcane - Xiuting Hua; Zhen Li; Meijie Dou; Yanqing Zhang; Dongxu Zhao; Huihong Shi; Yihan Li; Shuangyu Li; Yumin Huang; Yiying Qi; Baiyu Wang; Qiyun Wang; et al. (Planta, 2024)

Corrigendum to “Horizontal transfer of antibiotic resistance genes within the bacterial communities in aquacultural environment” [Sci. Total Environ. 820 (2022) 153286] - Songzhe Fu; Qingyao Wang; Rui Wang; Yixiang Zhang; Ruiting Lan; Fenglan He; Qian Yang (Science of The Total Environment, 2024)

Global meta-analysis and three-year field experiment shows that deep placement of fertilizer can enhance crop productivity and decrease gaseous nitrogen losses - Peng Wu; Qi Wu; Hua Huang; Lin Xie; Haoyuan An; Xintong Zhao; Fangtao Wang; Ziting Gao; Ruiting Zhang; Kemoh Bangura; Jianfu Xue; Min Sun; et al. (Field Crops Research, 2024)

Scrub-vegetation cover impact on soil water migration and temperature change during freeze–thaw events in sandy desert soils of northwest China - Shuai He; Chengfu Zhang; Fan-Rui Meng; Charles P.-A. Bourque; Zhenying Huang; Xiang Li; Ruiting Jia (CATENA, 2024)

Genotype diversity enhances invasion resistance of native plants via soil biotic feedbacks - Cai Cheng; Zekang Liu; Qun Zhang; Xing Tian; Ruiting Ju; Bo Li; Mark van Kleunen; Jonathan M. Chase; Jihua Wu (Ecology Letters, 2024)
Although native species diversity is frequently reported to enhance invasion resistance, within‐species diversity of native plants can also moderate invasions. While the positive diversity–invasion resistance relationship is often attributed to competition, indirect effects mediated through plant–soil feedbacks can also influence the relationship. We manipulated the genotypic diversity of an endemic species, Scirpus mariqueter , and evaluated the effects of abiotic versus biotic feedbacks on the performance of a global invader, Spartina alterniflora . We found that invader performance on live soils decreased non‐additively with genotypic diversity of the native plant that trained the soils, but this reversed when soils were sterilized to eliminate feedbacks through soil biota. The influence of soil biota on the feedback was primarily associated with increased levels of microbial biomass and fungal diversity in soils trained by multiple‐genotype populations. Our findings highlight the importance of plant–soil feedbacks mediating the positive relationship between genotypic diversity and invasion resistance.

Transcription profiles and phenotype reveal global response of Staphylococcus aureus exposed to ultrasound and ultraviolet stressors - Yun Bai; Yuanhang Zhou; Ruiting Chang; Xueli Hu; Yingying Zhou; Jiabo Chen; Zhi Zhang; Juanjuan Yao (Science of The Total Environment, 2024)

Investigating synergism and mechanism during sequential inactivation of Staphylococcus aureus with ultrasound followed by UV/peracetic acid - Yun Bai; Yuanhang Zhou; Ruiting Chang; Yingying Zhou; Xueli Hu; Jiawei Hu; Chuanyao Yang; Jiabo Chen; Zhi Zhang; Juanjuan Yao (Journal of Hazardous Materials, 2024)

An attomolar-level electrochemical DNA biosensor based on target-triggered and entropy-driven catalytic amplification integrated with AuNPs@ZIF-8 nanocomposites for oral cancer overexpressed 1 detection - Jing Li; Qi Jiang; Minhui Chen; Wei Zhang; Ruiting Liu; Jin Huang; Qin Xu (Analytica Chimica Acta, 2024)

The role of total antioxidant capacity and malondialdehyde of seminal plasma in the association between air pollution and sperm quality - Lipeng Li; Tengfei Feng; Ruiting Wu; Yaling Zhang; Ning Wang; Mengqi Wu; Yaxian Pang; Sujuan Yang; Aimin Yang; Dengsuo Zhang; Guimin Hao; Rong Zhang (Environmental Pollution, 2023)

Chitosan-based mussel-inspired hydrogel for rapid self-healing and high adhesion of tissue adhesion and wound dressings - Yongyan Yang; Ying Ma; Jingfei Wang; Liru You; Ruiting Zhang; Qingye Meng; Shuangling Zhong; Wenqi He; Xuejun Cui (Carbohydrate Polymers, 2023)

Maternal tamoxifen exposure leads to abnormal primordial follicle assembly - Jinxin Zhao; Jiaona Zhang; Yonghong Sun; Ruiting Wang; Dachuan Shi; Wei Shen; Xiaofeng Sun (Histochemistry and Cell Biology, 2023)

Rapid and sensitive detection of methyl parathion in rice based on carbon quantum dots nano-fluorescence probe and inner filter effect - Ruiting Zhang; Liyuan Zhang; Runzhong Yu; Changyuan Wang (Food Chemistry, 2023)

High adhesion hydrogel electrolytes enhanced by multifunctional group polymer enable high performance of flexible zinc-air batteries in wide temperature range - Zhihao Shang; Hang Zhang; Mengfei Qu; Ruiting Wang; Li Wan; Da Lei; Zhengzheng Li (Chemical Engineering Journal, 2023)

Enhanced inactivation of Escherichia coli by ultrasound combined with peracetic acid during water disinfection - Yun Bai; Chunhai Shi; Yuanhang Zhou; Yingying Zhou; Haocheng Zhang; Ruiting Chang; Xueli Hu; Jiawei Hu; Chuanyao Yang; Kedi Peng; Ping Xiang; Zhi Zhang (Chemosphere, 2023)

Linear charging-discharging of an ultralong UVA persistent phosphor for advanced optical data storage and wide-wavelength-range detector - Chuanlong Wang; Yahong Jin; Jiaxin Zhang; Xiangguang Li; Haoyi Wu; Ruiting Zhang; Qing Yao; Yihua Hu (Chemical Engineering Journal, 2023)

Moderate physical activity against effects of short-term PM2.5 exposure on BP via myokines-induced inflammation - Mengqi Wu; Yaxian Pang; Meiyu Chen; Lipeng Li; Lina Yan; Jie Ning; Qingping Liu; Yaling Zhang; Tao Jiang; Aijuan Kang; Xiaoyan Huang; Wentao Hu; et al. (Science of The Total Environment, 2023)

Insight into core -shell microporous zinc silicate adsorbent to eliminate antibiotics in aquatic environment under the COVID-19 pandemic - Xueli Hu; Yuanhang Zhou; Yingying Zhou; Yun Bai; Ruiting Chang; Peng Lu; Zhi Zhang (Journal of Cleaner Production, 2023)

Fine-mapping and candidate gene analysis of qFL-c10-1 controlling fiber length in upland cotton (Gossypium hirsutum L.) - Ruiting Zhang; Chao Shen; De Zhu; Yu Le; Nian Wang; Yuanxue Li; Xianlong Zhang; Zhongxu Lin (Theoretical and Applied Genetics, 2022)

Nebulization Therapy with Umbilical Cord Mesenchymal Stem Cell-Derived Exosomes for COVID-19 Pneumonia - Meiping Chu; Hao Wang; Linjie Bian; Jiehui Huang; Danping Wu; Ruiting Zhang; Fangli Fei; Yigang Chen; Jiazeng Xia (Stem Cell Reviews and Reports, 2022)
Background Scientists have been facing numerous challenges in the development of an effective therapeutic strategy for the treatment of COVID-19 pneumonia. Several studies have suggested that improving patient immunity and reducing lung injury induced by SARS-CoV-2 may be effective for treating patients with COVID-19. Methods A pilot trial of nebulization therapy with exosomes of mesenchymal stem cells (MSCs) was performed on seven patients with COVID-19 pneumonia. Exosomes secreted from MSCs were collected and purified using multiple ultrafiltration steps. All patients were treated with nebulization of MSC-derived exosomes, and primary safety and efficacy outcomes were evaluated. Results Our clinical study demonstrated that nebulization of MSC-derived exosomes is a novel method that might be utilized in the treatment of COVID-19 pneumonia. Nebulization of MSC-derived exosomes did not induce acute allergic or secondary allergic reactions but did promote the absorption of pulmonary lesions and reduce the duration of hospitalization for mild cases of COVID-19 pneumonia. Conclusions Nebulization of MSC-derived exosomes is a safe, effective, and simple method, and their application at the beginning of treatment may be more beneficial. Trial Registration Chinese Clinical Trial Registry, ChiCTR2000030261. Registered on 26 February 2020. Graphical Abstract

White Matter Free Water is a Composite Marker of Cerebral Small Vessel Degeneration - Peiyu Huang; Ruiting Zhang; Yeerfan Jiaerken; Shuyue Wang; Hui Hong; Wenke Yu; Chunfeng Lian; Kaicheng Li; Qingze Zeng; Xiao Luo; Xinfeng Yu; Xiao Wu; et al. (Translational Stroke Research, 2022)

Effects of seasonal ambient heat stress on expression of microRNAs in the mammary gland of Holstein cows - Caiyun Fan; Ruiting Hu; Haixiao Fan; Ying Yang; Bin Gong; Shaoze Zhang; Jianping Ding; Yanjing Su; Zhao Zhuo; Jianbo Cheng (International Journal of Biometeorology, 2021)

Effect of different carboxymethyl cellulose structure parameters on tartrates stability of red wine: viscosity and degree of substitution - Haiyan Ding; Ruiting Hou; Yun Li; Beibei Zhang; Baobao Zhao; Kun Liu (Food Additives & Contaminants: Part A, 2020)

Perfusion Changes of Unexplained Early Neurological Deterioration After Reperfusion Therapy - Jingjing Fu; Ying Zhou; Qingqing Li; Genlong Zhong; Sheng Zhang; Ruiting Zhang; Chang Liu; Minming Zhang; Min Lou (Translational Stroke Research, 2020)

The assessment of different vegetation indices for spatial disaggregating of thermal imagery over the humid agricultural region - Kai Liu; Shudong Wang; Xueke Li; Yao Li; Bo Zhang; Ruiting Zhai (International Journal of Remote Sensing, 2020)

Hydrophobin HFBII-4 from Trichoderma asperellum induces antifungal resistance in poplar - Huifang Zhang; Shida Ji; Ruiting Guo; Chang Zhou; Yucheng Wang; Haijuan Fan; Zhihua Liu (Brazilian Journal of Microbiology, 2019)

ALIX increases protein content and protective function of iPSC-derived exosomes - Ruiting Sun; Yingying Liu; Meng Lu; Qianqian Ding; Pingping Wang; Heng Zhang; Xiaoyu Tian; Peng Lu; Dan Meng; Ning Sun; Meng Xiang; Sifeng Chen (Journal of Molecular Medicine, 2019)

Characterization of the complete chloroplast genome sequence of Cardamine macrophylla (Brassicaceae) - Ting Ren; Yanci Yang; Jiao Wang; Ruiting Zhang; Zhan-Lin Liu (Conservation Genetics Resources, 2018)

Complete chloroplast genome sequence of Pedicularis cheilanthifolia, an alpine plant in China - Ruiting Zhang; Jiao Wang; Kai Han; Ting Ren; Shuyun Zeng; Edward Biffin; Zhan-Lin Liu (Conservation Genetics Resources, 2017)

Characterization of the complete chloroplast genome of the Cortusa matthioli subsp. pekinensis (Primulaceae) - Jiao Wang; Ruiting Zhang; Ting Ren; Kai Han; Shuyun Zeng; Edward Biffin; Zhan-Lin Liu (Conservation Genetics Resources, 2017)

A global synthesis of below‐ground carbon responses to biotic disturbance: a meta‐analysis - Baocheng Zhang; Xuhui Zhou; Lingyan Zhou; Ruiting Ju (Global Ecology and Biogeography, 2015)
Aim Climate change, especially the wider occurrence of extreme events, is likely to increase the intensity and frequency of insect/pathogen outbreaks (referred to as biotic disturbance), which may considerably affect plant ecophysiological traits and thus the ecosystem carbon ( C ) cycle. Little is known, however, about the ways in which biotic disturbance quantitatively affects ecosystem C processes, especially those that occur below ground. We reveal the general patterns of below‐ground C responses to biotic disturbance from field manipulative experiments and opportunistic events. Location Global. Method We carried out a meta‐analysis examining the effects of biotic disturbance on 16 variables associated with below‐ground C processes, based on 64 experimental studies. Results Biotic disturbance significantly decreased below‐ground C pools with relatively long residence times (e.g. root biomass and soil organic carbon, SOC ), but increased labile C pools (e.g. microbial biomass carbon, MBC ; dissolved organic carbon, DOC ), soil respiration ( R s ) and its components, and microbial population sizes. Compared with the neutral or positive effects of other environmental changes on below‐ground C pools and fluxes, biotic disturbance had a negative effect on plant biomass and SOC but a larger positive effect on MBC , DOC and R s . Main conclusions Biotic disturbance can have stronger impacts on below‐ground C processes than other environmental changes, and the sensitive responses of soil labile C pools and C fluxes to biotic disturbance decrease long‐term below‐ground C sequestration. More research efforts are, however, needed to reduce the uncertainties in quantifying the effects of biotic disturbance and to improve forecasting of the feedback between the carbon cycle and climate.

Equilibrium mechanism analysis on the physical processes of IAP3.0 - Zuo Ruiting; Wang Liqiong; Zeng Qingcun; Zhang Ming (Advances in Atmospheric Sciences, 2005)